Case Report: Complete Maternal Uniparental Disomy of Chromosome 2 With a Novel UNC80 Splicing Variant c.5609-4G> A in a Chinese Patient With Infantile Hypotonia With Psychomotor Retardation and Characteristic Facies 2 - Tao, Yilun; Han, Dong; Wei, Yiju; Wang, Lihong; Song, Wenxia; Li, Xiaoze (Frontiers in Genetics, 2021)
Background: Infantile hypotonia with psychomotor retardation and characteristic facies 2 (IHPRF2) is a rare autosomal recessive neurodevelopmental disorder caused by mutations in the UNC80 gene. It is characterized by severe global developmental delay, poor or absent speech and absent or limited walking abilities. The current study explored a case of a Chinese patient with IHPRF2 caused by a novel splicing variant of UNC80. Case Report: The proband is a 8-year-old Chinese male manifested with global developmental delay, severe truncal hypotonia, absent speech and intellectual disability. SNP array analysis revealed a uniparental isodisomy of the entire chromosome 2 [UPD(2)] in the proband. Whole exome sequencing (WES) subsequently identified a novel mutation c.5609-4G>A in the UNC80 gene, which was inherited from his mother and was confirmed by Sanger sequencing, indicating that UPD(2) was of maternal origin. Conclusion: A novel UNC80 homozygous splicing variant c.5609-4G>A associated with maternal UPD(2) was identified. These findings indicate that UPD poses a high risk of autosomal recessive diseases, and provides information on the variant spectrum for UNC80. Our findings elucidate on understanding of the genotype-phenotype associations that occur in IHPRF2 patients.